Case report: The first known case of male retroperitoneal mesonephric-like adenocarcinoma - Hu, Baohong; Liu, Ying; Tang, Jingjing (Frontiers in Oncology, 2024)
AimWe aimed to analyze the clinico-pathological and molecular features of mesonephric-like adenocarcinoma (MLA) to enhance understanding of this tumor type.MethodsThis is the first case of MLA occurring in the retroperitoneum of a male patient. Clinico-pathological and molecular characteristics were analyzed, and the relevant literature was reviewed.ResultsA 65-year-old elderly male was admitted to the hospital with mild bilateral dull pain in the lumbar region for more than 1 month, accompanied by a feeling of dysuria. CT tomography revealed a retroperitoneal tumor. While tumor immuno-histochemistry was positive for CK, CK7, Vimentin, PAX-8, CD10, GATA-3, EMA, and CR to varying degrees, it was negative for P53, WT-1, HMB45, MelanA, CD117, DOG-1, CD34, S-100, ER, PR, AR, CEA, α-inhibin and TTF-1. Ki67 index was <10% in most areas and was approximately 30% in the hotspot areas in the glandular ductal region. Molecular detection (Next-generation sequencing method, 425-gene panel from NanjingShihe Gene Biotechnology Co., Ltd. for targeted DNA enrichment): No clinically significant variants detected. The final pathological diagnosis was a retroperitoneal malignant tumor consistent with a well-moderately differentiated MLA.ConclusionMLA in the retroperitoneum of men has not been reported yet. The diverse morphology and unclear molecular characteristics of this tumor mandate careful diagnosis for good clinical outcomes.